Growth Performance, Mortality, and Blood Biochemistry of Broiler Chickens Supplemented with Cypress and Juniper Essential Oils - Amor Fellahi; Ikram Toumi; Ifriqya Medila (Journal of Animal and Plant Sciences, 2026)
<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; line-height: 115%; font-family: 'Times New Roman',serif; mso-fareast-font-family: Aptos; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The objective of the present study was to investigate the effects of cypress (<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; line-height: 115%; font-family: 'Times New Roman',serif; mso-fareast-font-family: Aptos; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Cupressus sempervirens <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; line-height: 115%; font-family: 'Times New Roman',serif; mso-fareast-font-family: Aptos; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">L.) and juniper (<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; line-height: 115%; font-family: 'Times New Roman',serif; mso-fareast-font-family: Aptos; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Juniperus communis <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; line-height: 115%; font-family: 'Times New Roman',serif; mso-fareast-font-family: Aptos; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">L.) essential oils (EOs), alone and in combination, on the growth performance and blood biochemical parameters of commercial broilers (Arbor Acres Plus) under natural health challenge. A total of 480 one-day-old chicks were randomly allocated following a completely randomized design into five treatment groups (96 per group; 8 replicates of 12 birds each). Birds in the negative control (NC) group were fed a <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; line-height: 115%; font-family: 'Times New Roman',serif; mso-fareast-font-family: Aptos; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">corn-soybean<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; line-height: 115%; font-family: 'Times New Roman',serif; mso-fareast-font-family: Aptos; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> meal diet and provided plain water (total solids of 1085 mg/L) without additives. The positive control (PC) group was fed the same diet supplemented with an antibiotic growth promoter (AGP) and additionally received two antibiotic treatments via drinking water following a colibacillosis outbreak during the trial; this group was therefore not considered a pure AGP control, limiting its suitability as a benchmark for growth performance. The essential oil-treated groups were supplemented with cypress (CEO), juniper (JEO), and a mixture of both (MEO), administered at a concentration of 625 ppm in a pulsed cycle of three days on and three days off, repeated throughout the 42-day trial. Mortality increased during the trial, with significantly higher rates (P ≤ 0.05) in the PC group. CEO Supplementation was associated with improved feed conversion ratio (FCR) at day 35 and significantly enhanced survivability and European Production Efficiency Factor (EPEF) (P ≤ 0.05). On day 42, serum biochemical analysis revealed significantly lower total cholesterol and LDL concentrations in the JEO group, whereas the MEO group exhibited the lowest triglyceride and creatinine levels (P ≤ 0.05). In summary, CEO primarily improved EPEF through enhanced survivability, while JEO and MEO favorably modulated lipid metabolism and renal markers. These findings suggest that cypress and juniper EOs could serve as an effective prophylactic strategy against colibacillosis outbreaks in broilers.
Keywords: Broiler chicken; Cypress; Disease challenge; Essential oil; European Production Efficiency Factor; Juniper.